Acute Effects of Different Electroacupuncture Point Combinations to Modulate the Gut-Brain Axis in the Minipig Model. (20th October 2022) - Zhang, Xuwen; Guérin, Sylvie; Launay, Youenn; Serrand, Yann; Coquery, Nicolas; Val-Laillet, David
Abstract : This study aimed to compare the gut-brain axis responses to acute electroacupuncture (EA) at different acupoint combinations in the minipig model. Four adult Yucatan minipigs were subjected twice to four acute EA treatments (25-minute acute sessions) including sham (false acupoints) and control (no EA), during anesthesia and according to a Latin-square design paradigm. Acupoint combinations (4 loci each) are head-abdomen (#70 Dafengmen, #35 Sanwan), back (bilateral #27 Pishu, #28 Weishu), leg (bilateral #79 Hangou, #63 Housanli), and sham (2 bilateral points that are not acupoints). Electrocardiograms were performed to explore heart rate variability (HRV). Infrared thermography was used to measure skin temperature at the stimulation points. Saliva (cortisol) and blood samples (leptin, total/active ghrelin, insulin, and glucose) were collected for further analyses before and after acute EA. All animals were also subjected to BOLD fMRI to investigate the brain responses to EA. Acute EA significantly modulated several physiological and metabolic parameters compared to basal, sham, and/or control conditions, with contrasting effects in terms of BOLD responses in brain regions involved in the hedonic and cognitive control of food intake. The head-abdomen combination appeared to be the most promising combination in terms of brain modulation of the corticostriatal circuit, with upregulation of the dorsolateral prefrontal cortex, dorsal striatum, and anterior cingulate cortex. It also induced significantly lower plasma ghrelin levels compared to sham, suggesting anorectic effects, as well as no temperature drop at the stimulation site. This study opens the way to a further preclinical trial aimed at investigating chronic EA in obese minipigs.